Иммунофлуоресцентный анализ нарушений в структуре синаптонемных комплексов, вызванных ксенобиотиками в сперматоцитах мыши - Ацаева, М.М.; Коломиец, О.Л. (Фактори експериментальної еволюції організмів, 2013)
Aims. The aim of this study was a comparative analysis of the effects of 1,1-dimethyl hydrazine (1,1-DMH) – a component of rocket fuel, and anti-cancer drug cyclophosphan (CP) to the structure of the synaptonemal complex (SC) of male mice and selection of the defective spermatocytes I at meiosis. Methods. Immuno-fluorescent analysis of the structure of SC damage and chromatin silencing. Results. Multiple damage in the structure of the SCs or even the absence of SC has been detected at the spermatocytes nuclei after the introduction of 1,1-DMH and CP tо male mice. The most common damage were fragmentation of SCs, the disturbance of the chromosome synapsis and architectonics of the nuclei. Ring chromosome and SCP3 protein aggregates were also found. There were every indication of pachytene arrest at many nuclei. We revealed morphological features, the so-called meiotic catastrophe that blocked meiosis at the different stages of meiosis. Conclusions. 1,1-DMH and CP cause dramatic damage of meiotic chromosomes, which carries a risk of disruption of spermatogenesis, infertility and risk of chromosomal aberrations of offspring, as evidenced by the detection of abnormal sperm.